Wayward women : sexuality and agency in a New Guinea society - Wardlow, Holly (University of California Press, 2006)
Analyzes female agency, gendered violence, and transactional sex in contemporary Papua New Guinea. Focusing on Huli "passenger women," this work explores the socio-economic factors that push women into the practice of transactional sex, and asks how these transactions might be an expression of resistance, or even revenge